Students’ Resiliency towards Experiencing Tornado - Banal, Ariel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study was conducted to find the meaning of resilience for students experiencing tornadoes. To attain the meaning of fear for a person with traumatic injury, to know the common effects of experiencing a tornado. To accomplish the reason for the study, the phenomenological method was used to comprehend and interpret the meaning of experiences of student's life when they experienced a tornado. The learners of one of the leading private schools in the Division of Pampanga-Philippines served as the informants of the study. Results revealed that the majority of the learners’ state that resiliency is a type of adaptability wherein they were able to adapt to the changes in their surroundings, on how they can stand regardless of what they have encountered, they were able to overcome it and that made them a resilient person. The researchers conducted an interview wherein most of their informants’ state that the fear and trauma they got from experiencing a tornado affects their lives. It can hinder someone from achieving their goals, they fear something they want to try because most of them state that it might happen again, it might cause them danger again, and they overthink just a wind that they think, another tornado will come again. When it comes to the effects of experiencing a tornado, most of them stated that they got scared and traumatized. Despite all the negative effects, tornados changed their perspective on life. It also recommended that parents and teachers provide comfort, counseling, and monitoring of learners' behavior.